Evaluation of the blood lipid profile pattern in female breast cancer patients in Jordan. - Alsarhan, Ali; Ata Alsarhan, Ali; Al Odat, Ibrahim; Khwaldeh, Alia; Al Shara, Baker (Nutrición Clínica y Dietética Hospitalaria, 2024)
Background: Breast cancer is a cancerous growth impacting approximately 2.26 million women globally, The World Health Organization reports that it is thought to be the tumor in women that is diagnosed the most commonly. development.Objective: Examining any possible correlation between serum lipid concentrations and the cancer of the breast in a community sample of Jordanian women is the primary goal of the current investigation.Methods: In this study 122 subjects were included, patient group consists of 94 women diagnosed breast cancer, where control group consists of 28 healthy women. Samples of Venous blood were collected from participant’s subjects, after centrifugation obtained serum was used for assessment of Triglycerides, total cholesterol, and HDL –cholesterol levels using fully automated analyzer for biochemistry. The Fried Wald equation was applied for calculating serum concentrations of LDL-Cholesterol Results: After comparison with control group, a strong positive significant notable elevation was observed between the BMI values of the breast cancer patients. (28.8 ± 3.9 vs. 25.2 ± 4.3 kg/m2, p >0.005). The patient group's serum levels of total cholesterol and triglycerides were observed to be considerably higher than those of the control group. (230.7 ± 86.9 vs. 177.6 ± 44.5 mg/dL, p >0.005) and (209.4 ± 95.9 vs. 175.7 ± 45.6 mg/dL, p >0.005) respectively. On other hand, the patients' group's blood LDL-cholesterol levels were found to be higher (122.8 ± 25.5 vs. 115.9 ± 26.9mg/dL, p >0.005). There was no notable alteration in Serum HDL-Cholesterol levels among the two group.Conclusion: The current study's results indicate a clear correlation between increased body mass index (BMI), altered lipid profiles, and an increasing of risk of breast cancer in women living in Jordan.